KEEFEKTIFAN HASIL BELAJAR SISWA KELAS IV SDN 1 MENAWAN PADA MATA PELAJARAN PENDIDIKAN PANCASILA MENGGUNAKAN MODEL PROBLEM BASED LEARNING - Mustaqim, Noor; Ika Ari Pratiwi; Ika Oktavianti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study was to measure the effectiveness of the use of the Problem Based Learning (PBL) Model in the Pancasila Education subject of grade IV students of SDN 1 Menawan. This quantitative research was conducted using an experimental method. This research was conducted using a quantitative one-group pretest-posttest design. This study used a paired sample t-test to determine how signifi20kii202133299@std.umk.ac.id 2133299@std.umk.ac.id cant the effect of increasing learning outcomes was on the pretest and posttest. The results of the paired sample t-test analysis showed that the level of significance obtained was a significance value of -47.233. The results of the N-Gain test calculation showed that the N-Gain score reached 0.7529 which was classified as high. While the percentage results of the N-Gain obtained an average of 75.29 which can be interpreted as quite effective. The Problem-Based Learning model has proven to be quite effective in improving students' learning outcomes in the subject of Pancasila Education, because with the Problem Based Learning (PBL) model, students are more active in working on LKPD questions, discussing and presenting during the learning process.